Profile Review of Grapes Horticulture Cultivation in the Buleleng - Sri Mulyani; Bambang Admadi; Ketut Satriawan; Made Hendra Mardiana (Agroindustrial Journal, 2017)
Buleleng as a centre of grape commodity in Bali has experienced a decrease in the number of grapes production. Grapes horticultural profile should be made based on 6 (six) pillars of the horticulture development. The aim of this study is to determine cultivation profile of the grapes horticulture in Buleleng. This research uses purposive sampling method to determine sample location. The respondents consist of farmers, stakeholders and other relevant agencies which chosen by using random sampling method. The results show respondents’ opinion related to the pillar program compatibility and incompatibility: 1) development of horticultural area 78.88% and 20.00%, 2) application of GAP / SOP 68.88% and 29.63%, 3) implementation of supply chain management (SCM) 59.10% and 40.90%, 4) implementation of integrated horticultural facility 64.18% 33.32%, 5) Institutional development 19.99% and 79.18%, and 6a) increase on horticultural consumption 44.06% and 51.48%, while 6b) on the export acceleration 7.91% and 92.09%. Based on the six pillars development program implementation, only four programs namely program 1, 2, 3, and 4 that have high average of compatibility (67.76%) while the other two programs, namely the program 5 and 6 have lower average of compatibility (22.99%).